2000
DOI: 10.1016/s0379-6779(99)00363-x
|View full text |Cite
|
Sign up to set email alerts
|

Switching effect in poly(p-phenylenevinylene)

Abstract: A switching effect was investigated in poly p-phenylenevinylene PPV . N-shaped current-voltage I-V characteristics of thick ITO-PPV-Al structures were observed, which correspond to switching at a threshold voltage typically in the range 2-5 V from a conducting to a resistive state. The behaviour was independent of the polarity of the applied voltage and the sweep direction. At the threshold voltage, the current changes by approximately one and a half orders of magnitude of its previous value. Pulsed measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Several organic materials, e.g. Rose Bengal [161], 2,3-dichloro-5,6-dicyano-1,4-benzoquinone [184], p-phen ylenevinylene [185], conjugated copolymer containing fluorine and chelated europium complex [186], also exhibit resistive switching natures and are potential candidates for RRAMs. However, many switching organic materials are very often in contact with Al electrodes [161,184,185].…”
Section: Carbon-based Materials and Other Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several organic materials, e.g. Rose Bengal [161], 2,3-dichloro-5,6-dicyano-1,4-benzoquinone [184], p-phen ylenevinylene [185], conjugated copolymer containing fluorine and chelated europium complex [186], also exhibit resistive switching natures and are potential candidates for RRAMs. However, many switching organic materials are very often in contact with Al electrodes [161,184,185].…”
Section: Carbon-based Materials and Other Materialsmentioning
confidence: 99%
“…Rose Bengal [161], 2,3-dichloro-5,6-dicyano-1,4-benzoquinone [184], p-phen ylenevinylene [185], conjugated copolymer containing fluorine and chelated europium complex [186], also exhibit resistive switching natures and are potential candidates for RRAMs. However, many switching organic materials are very often in contact with Al electrodes [161,184,185]. In fact, Karthäuser et al have pointed out that switching cells utilizing Al electrodes probably show the resistive switching effect of the interfacial AlO x layers rather than these organic films [161].…”
Section: Carbon-based Materials and Other Materialsmentioning
confidence: 99%
“…Trap recharging, diffusion of mobile ions, formation and dissociation of bipolarons in the accumulation layer should be considered [20]. Considering nature of the negative resistance phenomena observed in present study for some samples it should be mentioned, that negative differential resistance effect was already reported for some organic semiconductor based structures [22][23][24][25][26]. Considering nature of the negative resistance phenomena observed in present study for some samples it should be mentioned, that negative differential resistance effect was already reported for some organic semiconductor based structures [22][23][24][25][26].…”
Section: Comparison Of I-v Characteristics Of Metal/organic Semicondumentioning
confidence: 59%
“…The first one is trapping and de-trapping of carriers [22]. In the case of the bottom-contact organic semiconductor devices not only bulk of the organic semiconductor, but organic semiconductor/ /electrode interface has significant influence on formation of the microconducting filament as well [24]. In such a case at low voltages current flow via spatially localized pathways and as a result increased current strength is observed [22 -26].…”
Section: Comparison Of I-v Characteristics Of Metal/organic Semicondumentioning
confidence: 99%
“…In recent years, the resistive switching (RS) effect has drawn enormous attention from both academic and industrial communities due to its interesting physics as well as promising applications. It has been demonstrated that a wide variety of materials, such as metal oxides, chalcogenides, and organic materials, show RS behavior. So far the mechanisms of RS, which are related to some important scientific issues and also significant for applications of RS, have not been solved .…”
Section: Introductionmentioning
confidence: 99%